When Everyone Wins? Exploring Employee and Customer Preferences for No-Haggle Pricing - Kniffin, Kevin M.; Reeves-Ellington, Richard; Wilson, David S. (Frontiers in Psychology, 2018)
The organizational importance for interactions between frontline employees and customers has been examined in relation to dimensions such as climate or culture. In this article, we highlight the importance of pricing strategies – typically studied in relation to consumer preferences – for frontline employees. To do this, we apply an evolutionary perspective and present two complementary studies that focus on the relevance of price discipline in relation to employee attitudes and preferences. Focusing on the industry of new automobile sales since there is important firm-level pricing variation, Study 1 finds a faintly positive relationship among employee prosociality, customer satisfaction, and fixed or “no-haggle” pricing strategies. In Study 2, participants indicated a preference for working in environments that offered the same, non-disparate prices to all customers. While previous research has examined the relationships between employee and customer attitudes in relation to firm performance, our studies emphasize the role that pricing strategies can play as a mechanism in those relationships. Our studies illustrate the value of evolutionary frameworks for contemporary business problems.